Cybernetics and Automation Control Theory Methods in Intelligent Algorithms Proceedings of 8th Computer Science On-line Conference 2019, Vol. 3 - Silhavy, Radek; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book discusses novel intelligent-system algorithms and methods in cybernetics, presenting new approaches in the field of cybernetics and automation control theory. It constitutes the proceedings of the Cybernetics and Automation Control Theory Methods in Intelligent Algorithms Section of the 8th Computer Science On-line Conference 2019 (CSOC 2019), held on-line in April 2019. .
Novel Filtering-based Approach using Fuzzy Logic for Prevention of Adversaries in Sensory Application -- Game-Decision Model for Isolating Intruder & bridging Tradeoff between Energy and Security -- Simplified Framework for Resisting Lethal Incoming Threats from Polluting in Wireless Sensor Network -- An Efficient Approach towards Formal Verification of Mixed Signals using Feed-Forward Neural Network -- PCCV: Parallel Cancellation and Convolution Viterbi encoding/decoding approach for MIMO-OFDMA for efficient resource allocation and power consumption -- Streaming Analytics - Real-time Customer Satisfaction in Brick-And-Mortar Retailing -- An Efficient Mechanism to Improve the Complexity and System Performance in OFDM using Switched Beam Smart Antenna -- Modeling the Engineering Process as a Thinging Machine: A Case Study of Chip Manufacturing -- A Simple and Cost-Effective Anomaly Detection Paradigm on the Basis of Computational Intelligence for Mobile Ad-hoc Networks from a Security Viewpoint -- A Technique of Adaptation of the Workload Distribution Problem Model for the Fog-Computing Environment.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence